Uji Aktivitas Anti Jamur Ekstrak Etanol Daun Pepaya Jepang (Cnidoscolus Aconitifolius) terhadap Pertumbuhan Malassezia Furfur - Mhd Alhafiz Siddiq Nasution; Susi Sembiring; Runggu Retno Justiani Napitupulu (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2026)
Malassezia furfur is an opportunistic fungus associated with various skin disorders, including pityriasis versicolor and seborrheic dermatitis. Long-term use of synthetic antifungal agents may lead to side effects and drug resistance, highlighting the need for alternative treatments derived from natural sources. Japanese papaya leaves (Cnidoscolus aconitifolius) contain bioactive compounds such as flavonoids, alkaloids, and saponins, which are known to exhibit potential antifungal properties. This study aimed to evaluate the antifungal activity of the ethanol extract of Japanese papaya leaves against the growth of Malassezia furfur in vitro. This research employed a true experimental design using the diffusion method to measure inhibition zone diameters at concentrations of 25%, 50%, and 75%. Ketoconazole was used as a positive control, while the solvent served as a negative control. The results showed that the 75% concentration exhibited strong inhibitory activity with a mean inhibition zone of 10.82 mm, whereas the 25% and 50% concentrations demonstrated weak inhibitory effects. Although the extract showed lower activity compared to ketoconazole, it was significantly more effective than the negative control. In conclusion, the ethanol extract of Japanese papaya leaves has potential as a natural antifungal agent against Malassezia furfur, although its effectiveness remains lower than that of synthetic antifungal drugs.